The development of social interaction for early childhood in Lampang province by using virtual reality application - Muangmool, Somchai; Sirichaisin, Kedthip (Asian Journal of Education and Training, 2023)
The aim of this research was to develop social interaction for early childhood children in Lampang province, Thailand by using virtual reality technology. The population in this study was early childhood children from 355 schools in Lampang province, under the jurisdiction of Lampang Primary Educational Service Area 1, 2, and 3. The sample group consisted of sixty early childhood children who were selected by purposive selection. The research tools the application of Lampang learning resources and the early childhood social development evaluation form. The results were statistically analysed for percentages in the form of descriptive narrative. The results showed that the overall social development of the sample group was at the highest level or 76.58% with an average value of 4.53. Also, the results presented that the sample group was able to follow the rules and the agreements of the learning resources appropriately, give comments and answer the questions of the instructors. This was a result of using the VRLampang application which could be divided into three parts: 1) regulations and guidelines of the learning resources 2) information of ten Lampang learning resources 3) the efficient learning content activities appropriate for students.